The Local Wisdom Values in the Building Structure and Ornaments of the Witana Ward of Kanoman Palace Cirebon - Mahmud, Mahmud; Wirabhakti, Agus (CV. Publikasi Indonesia, 2024)
The popularity of the Witana Ward, Kanoman Palace, Cirebon, is still less popular than other buildings, even though the Witana ward is the forerunner of Cirebon civilization. The author intends to describe the Witana ward by exploring the values of the local wisdom contained in the building. Explorative approach is employed to obtain premier data such as literature review, observation and interviews. From this exploratory study resulted a description of the values of local wisdom in the Witana Ward namely (1) Candra Sengkala Figure, (2) Bird Logo, (3) Four Pillars, (4) Sun Symbol, (5) Symbol Of Kamangmang Dragon, (6) Dewandaru Tree, (7) Witana Well, (8) Lotus and Flowers Wijayakusuma, (9) A Gate, and (10) Wadasan and Megamendung. The local wisdom values are in the form of philosophy of life, ethics and morals, literature and culture, and religious advices. The symbolic meaning of wadasan teaches that humans must be as strong as a reef, sturdy even in the storm. While the megamendung symbol symbolizes a shady soul giving coolness. The wisdom that we can understand from the megamendung wadasan is an ethical and moral message.